2014-2017 Kansas Performance Tests with Field Pea Varieties - Haag, Lucas (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2018)
Spring field peas are a cool-season, grain legume crop that has emerged in recent years as a potential cash crop in northern Kansas. An official field pea variety testing program was established in 2014 to provide Kansas growers with unbiased performance comparisons of spring field pea varieties. From 2014-2016, the entries consisted entirely of yellow cotyledon type varieties. In 2017, several varieties of green field peas were entered, including CDC Greenwater, PSTSP28, and PSTSP29. Companies enter varieties of their choice and pay entry fees, which are used to cover the expenses of the testing program.
SRP1142
Keywords: SRP1142